Anthracene-fused porphyrins - Davis, N; Nicola K. S. Davis (2011)
This thesis describes the synthesis of a novel family of porphyrins fused to anthracenes, together with investigations into their optical and electrochemical properties, as well as exploring their potential for application in dye-sensitised solar cells. Chapter 1 gives an overview of the structure-property relationships of large planar pi- systems for organic electronic applications. Porphyrins are introduced as suitable building blocks for such systems, and approaches for extending the pi-conjugation of these macrocycles are presented. A literature review of porphyrins fused to aromatic units is presented in Chapter 2, with a focus on the influence of structure on the optoelectronic properties of such systems. The chapter concludes with a summary of my previous work on the synthesis of anthracene-fused porphyrins, and the aims of this project are stated. Chapter 3 describes the syntheses of fully and partially fused bis-anthracene porphyrin monomers and dimers. By varying peripheral substituents, it was possible to solve problems of aggregation encountered for these systems. Fusion of anthracene units to a porphyrin core was found to result in systems displaying strong absorption in the near-IR, small HOMO-LUMO gaps, and low oxidation potentials. Chapter 4 explores the synthesis, crystal structure and optoelectronic properties of a porphyrin fused to four anthracenes, revealing this system to exhibit the longest wavelength absorption of any porphyrin monomer. The synthesis of a liquid crystalline tetra-anthracene-fused porphyrin was proposed, and attempts to synthesise the necessary anthracene precursors were undertaken. Chapter 5 describes the molecular design and synthetic pathway to a mono-anthracene fused porphyrin, and its unfused analogue, for use in liquid electrolyte dye-sensitised solar cells. By varying the metal oxide layer or lithium ion concentration of the device, it was possible to achieve incident photon to current conversion efficiency (IPCE) responses at wavelengths beyond 1050 nm. Chapter 6 details the experimental synthetic procedures and characterisation data for all the compounds synthesised during this project.